A Comparative Study of Anxiety among Students from Rural and Urban Areas - Raghuveerprasad M. Raval; Dr. R. D. Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of this research study was to conduct a comparative study of anxiety of students from rural and urban areas. For this research study, students from Banaskantha rural area and Ahmedabad district urban area were selected as subjects. In this research study, a total of 24 students, 12 students from Banaskantha rural area and 12 students from Ahmedabad district urban area, were selected randomly. The S.C.A.T Sports Competition Anxiety Test questionnaire was selected as the measurement standard for the anxiety test. To compare the anxiety of students from rural and urban areas, the ‘t’ test was applied and the significance of the medians was tested at the 0.05 level. The conclusion was as follows. There was no significant difference in anxiety between the groups of students from Banaskantha rural area and Ahmedabad district urban area.